PENGARUH METODE PENGGARAMAN BASAH TERHADAP NILAI SENSORI IKAN LAYANG ASIN (Decapterus sp.) - Rieuwpassa, Frets Jonas; Lawendatu, Angryani Enjel; Mandeno, Jefri Anthonius; Tanod, Wendy Alexander; Cahyono, Eko; Ansar, Novalina Maya Sari; Sambeka, Yana; Tomasoa, Aprelia Martina (Universitas Teuku Umar, 2025)
The potential of flying fish (Decapterus sp.) in Sangihe is relatively abundant, yet the catch frequently cannot be absorbed by the market in the peak season. One alternative to overcome the excess catch is to process it into salted fish products. The quality of salted fish is highly dependent on salt concentration and soaking time. This study aimed to observe the effect of soaking time on the sensory quality of flying salted fish. This research was an experimental research with two treatments for the duration of soaking in salt solution with each treatment repeated three times. The research stages included making salted fish using 20% salt concentration with 12 and 24 hours of soaking. Furthermore, the sensory assessment was carried out (SNI no. 8273: 2016) with the parameters of appearance, taste, odor, and texture. Storage was carried out for 30 days at room temperature before being tested for the presence of mold. The results showed that the treatment of soaking time only had a real influence on the sensory value of the appearance of flying salted fish. In contrast, the soaking time did not affect the sensory values of odor (8,47±0,6-8,53±0,4), taste (8,33±0,9-8,40±0,6), and texture (7,87±0,7-7,93±1,0). After being stored for 30 days at room temperature, it was seen that mold had grown on flying salted fish. The study results showed that the 12-hour soaking time had a better value than the 24-hour soaking time.